Evaluasi Pewadahan Sampah Berdasarkan Perilaku Masyarakat (Studi Kasus: Kelurahan Karang Rejo Kota Balikpapan) - Nia Febrianti; Ismi Khairunnissa Ariani; Muhammad Rizqiawan Antul (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Transfer Station is one of the most important parts of waste management operational aspects. The condition of Transfer Station container is often neglected whether it meets the standards based on SNI 19-2454-2002 and Minister of Public Works Regulation Number 3 of 2013 concerning waste containers. The container of Transfer Station can be seen from the characteristics of it such as the shape, nature and material. Waste problems in Karang Rejo Village are caused by several factors such as the decrease in quality, the distribution of Transfer Station points, and community’s behaviour in disposing the solid waste. This study aims to analyze the distribution and provision of Transfer Station, analyze community behavior in disposing of waste and evaluate Transfer Station in Karang Rejo Village based on community behavior in waste disposal. This research is a qualitative research, the research procedures carried out are observation, identification of the provision and distribution of Transfer Station, analysis of Transfer Station conditions in a descriptive qualitative way, distribution and collection of questionnaires, data processing and the evaluation stage of waste containers according to people's behavior in disposing of waste. The results showed that in Karang Rejo Village there were 16 Transfer Station units where the distribution of it, was disproportionate, in terms of supply there were 8 out of 16 Transfer Station units whose buildings were in damaged condition (percentage <60%), 99% of the behavior of the Karang Rejo Village community in disposing of garbage by how to get off the vehicle and throw garbage into the Transfer Station and 90% of the Karang Rejo Village community did not know information about waste containers. The evaluation results showed that the Transfer Station in Karang Rejo Village was not in accordance with the standards and there were 10 units that required total renovation, and 6 units requires the addition of components such as lids on containers.